PENGARUH KUALITAS PELAYANAN DALAM JARINGAN APLIKASI INDIHOME TERHADAP KEPUASAAN PELANGGAN PADA PT TELKOM INDONESIA, TBK. DATEL BATURAJA - Levinia Susanti; Harby R Wiralaga; Yopi Yunsepa; Yuniarti Anwar (STIE DWI SAKTI BATURAJA, 2021)
This study entitled The Effect of Service Quality in the Indihome Application Network on Customer Satisfaction at PT Telkom Indonesia, Tbk. Datel Baturaja. With the formulation of the problem of how much influence the quality of service in the indihome application network on customer satisfaction at PT Telkom Indonesia, Tbk. Datel Bauraja. The research method uses descriptive methods, data collection techniques use interviews, observations, questionnaires, review documentation and literature study. As for the sampling technique used is simple random sampling technique with qualitative data analysis techniques and quantitative data analysis with research models in the form of multiple linear regression analysis, multiple correlation coefficient analysis, analysis of the coefficient of determination and hypothesis testing. Based on the results of the research conducted, it can be concluded that there is an effect of the variable efficiency (X1) fulfillment (X2) and availability (X3) on the customer satisfaction variable (Y) at PT Telkom Indonesia, Tbk. Datel Baturaja. As for the privacy variable (X4) there is no influence of the privacy variable (X4) on the customer satisfaction variable (Y) at PT Telkom Indonesia, Tbk. Datel Baturaja. Simultaneous testing states that there is an effect of variable efficiency (X1) fulfillment (X2), availability (X3) and privacy (X4) on the customer satisfaction variable (Y) at PT Telkom Indonesia, Tbk. Datel Baturaja.